2009
DOI: 10.1007/s10404-009-0483-9
|View full text |Cite
|
Sign up to set email alerts
|

Realistic Brownian Dynamics simulations of biological molecule separation in nanofluidic devices

Abstract: We present a Brownian Dynamics model of biological molecule separation in periodic nanofilter arrays. The biological molecules are modeled using the WormLike-Chain model with Hydrodynamic Interactions. We focus on short dsDNA molecules; this places the separation process either in the Ogston sieving regime or the transition region between Ogston sieving and entropic trapping. Our simulation results are validated using the experimental results of Fu et al. (Phys Rev Lett 97:018103, 2006); particular attention i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2010
2010
2025
2025

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 30 publications
1
22
0
Order By: Relevance
“…[13]; the focus of that paper was to demonstrate the feasibility of high-field electrophoresis and to highlight the importance of "torque assisted escape'' in the latter limit. More recently, Fayad and Hadjiconstantinou [14] developed a BD formulation based on the WLC [15] model in order to quantitatively model Ogston-regime separation; good agreement with the experimental results of Fu et al [3] was observed.…”
Section: Introductionsupporting
confidence: 52%
See 2 more Smart Citations
“…[13]; the focus of that paper was to demonstrate the feasibility of high-field electrophoresis and to highlight the importance of "torque assisted escape'' in the latter limit. More recently, Fayad and Hadjiconstantinou [14] developed a BD formulation based on the WLC [15] model in order to quantitatively model Ogston-regime separation; good agreement with the experimental results of Fu et al [3] was observed.…”
Section: Introductionsupporting
confidence: 52%
“…In other words, for an efficient model, some degree of coarse-graining is required. For the present application, BD simulations strike a good balance between fidelity and efficiency, and have already been used to model biological molecule separation [11][12][13][14]. Our approach places more emphasis on simplicity and efficiency which are essential in the context of device design and optimization.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To overcome these difficulties, it is common to use particle-based methods like Brownian dynamics [103] to simulate transport in micro-and nanofluidic devices [104], which can be run at a fraction of the cost as MD, but with the loss of atomic-scale precision.…”
Section: Chaptermentioning
confidence: 99%
“…Fayad and Hadjiconstantinou used BD simulation with WLC model considering HI to study the effect of device geometry on the separation process for shorter DNAs. Optimization of the device was also studied [109].…”
Section: Structured Microchannel Arrays For Entropic Trapmentioning
confidence: 99%